Spout diameter in fine particle conical spouted beds: Assessing the influence of draft tubes by PTV - Maider Bolaños; Xabier Sukunza; Mikel Tellabide; Idoia Estiati; Haritz Altzibar; Miriam Arabiourrutia; Martin Olazar (Chemical Engineering Journal Advances)
The spout diameter is an essential parameter for designing spouted bed contactors, as it conditions the gas–solid contact and heat and mass transfer rates. Several correlations have been proposed in the literature to estimate the spout size, but they do not provide accurate results in beds made up of fine particles, especially when they are equipped with open-sided draft tubes. Accordingly, the spout–annulus interface has been determined by means of Particle Tracking Velocimetry (PTV) and the spout shape has been delineated under different operating conditions in fountain confined conical spouted beds of varying geometric parameters. The air inlet diameter and gas velocity, as well as the aperture ratio of the open-sided draft tubes, are the parameters of greatest influence. Accordingly, a new correlation has been proposed, which allows predicting accurately the spout size in beds without draft tube, as well as those equipped with open-sided ones.